Impact of resource scarcity on general categorization tendency: The moderating role of perceived mutability. - Haowen Xiao; Jiayi Guo; Junyi Fang; Ting Xiao; Guocheng Li (PLoS ONE, 2023)
Prior studies revealed varying effects of resource scarcity on individuals' general categorization tendency. However, little is known about when and why such differences occur. Based on the self-regulatory model of resource scarcity, we examine whether resource scarcity generates higher or lower general categorization tendency depending on the perceived mutability of the resource discrepancy. We conducted two online experiments to test the hypotheses. The results affirmed that when individuals consider the resource discrepancy to be mutable, they are more likely to seek abundance to compensate for resource scarcity, thus reducing their general categorization tendency. In contrast, perceiving the scarcity as immutable triggers the intention to restore a sense of control undermined by the scarcity, increasing individuals' general categorization tendency. Our findings provide insights into the downstream consequences of resource scarcity and offer significant managerial implications for coping strategies.